From skies to markets implications of extreme weather events for macroeconomic and financial imbalances in CESEE countries - Meri Papavangjeli (Charles University in Prague, Institute of Economic Studies (IES), 2025)
This study explores the heterogeneous and asymmetric macro-financial effects of climate change in CESEE countries, depending on the level of underlying macrofinancial vulnerabilities. Focusing solely on acute physical risks - those arising from extreme weather events - it employs panel quantile regression analysis to examine data from 2000Q1-2022Q4 for 17 countries in the region. Notably, we find that climate shocks exacerbate macroeconomic and financial imbalances, increasing the susceptibility of already vulnerable economies to additional risks. Specifically, countries with higher economic imbalances suffer more severe output disruptions and heightened inflationary pressures following a climate shock. While the impact of climate shocks on external imbalances may be less pronounced, countries with existing vulnerabilities may still encounter pressures on trade and competitiveness. Additionally, climate shocks can intensify financial vulnerabilities for countries already grappling with lower levels of financial resilience.
Keywords: E52; E51; E61; E63; E65; 330; extreme weather events; macro-financial vulnerabilities; CESEE countries; panel quantile regression analysis